2010
DOI: 10.1309/ajcpazv88vifzsfd
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk HPV Testing in Women 30 Years or Older With Negative Papanicolaou Tests

Abstract: Cervical screening with combined cytology and high-risk human papillomavirus (HR-HPV) detection has been approved for women 30 years or older. We investigated the clinical use of cotesting for women with negative Papanicolaou tests. Follow-up cytology, HR-HPV test, and biopsy findings were identified during an 18-month period. In 1 year, 2,719 cotests from 2,686 women were identified; 146 were positive for HR-HPV. Among women with positive HR-HPV testing, 120 had follow-up, including 70 with repeated cotesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 13 publications
1
34
1
Order By: Relevance
“…HR-HPV DNA testing is recommended in combination with cytology in women 30 years or older and as a posttreatment follow-up test (37). In addition, HPV testing has proven to be useful for triage of the very problematic categories of equivocal cytological results that account for around half of abnormal results, such as atypical squamous cells of undetermined significance (ASC-US) (2).…”
mentioning
confidence: 99%
“…HR-HPV DNA testing is recommended in combination with cytology in women 30 years or older and as a posttreatment follow-up test (37). In addition, HPV testing has proven to be useful for triage of the very problematic categories of equivocal cytological results that account for around half of abnormal results, such as atypical squamous cells of undetermined significance (ASC-US) (2).…”
mentioning
confidence: 99%
“…To the best of our knowledge, there has been no similar previous report in the literature. Other groups have reported abnormalities detected by rescreening of negative cytology in women with concomitant positive hrHPV DNA test results [19,20]; however, these reports were not from the perspective of using an HPV test at follow-up as triage for colposcopy. An important strength of our study was that histological specimens were obtained on all participants, including patients with negative HPV tests.…”
Section: Discussionmentioning
confidence: 96%
“…These results are presented next as self-report (Murphy & Schwarz, 2007;Murphy, Schwarz & Dyer, 2008;Noller et al, 2003;Saint, Gildengorin, & Sawaya, 2005;& Yabroff et al, 2009) and actual practice (Tatsas, Phelan, Gravitt, Boitnott & Clark, 2012;Thrall et al, 2010).…”
Section: Adoptionmentioning
confidence: 99%
“…Two studies of actual ordering practices included in this review focused on HPV cotesting in women 30 years of age or older. Thrall et al (2010) reported that, if the guidelines were strictly followed, none of the women with dual negative results should have had repeat testing within the ensuing three-year period. However, after only 18 months, 51.8% had repeat cytology testing.…”
Section: Self-reportmentioning
confidence: 99%
See 1 more Smart Citation